Immune Features of Disparate Liver Transplant Outcomes in Female Hispanics With Nonalcoholic Steatohepatitis - Rebecca A. Sosa, PhD; Allyson Q. Terry, PhD; Takahiro Ito, MD; Bita V. Naini, MD; Ying Zheng, MS; Harry Pickering, PhD; Jessica Nevarez-Mejia, PhD; Ronald W. Busuttil, MD, PhD; David W. Gjertson, PhD; Jerzy W. Kupiec-Weglinski, MD, PhD; Elaine F. Reed, PhD; Fady M. Kaldas, MD (Transplantation Direct, 2023)
Background. Nonalcoholic steatohepatitis (NASH) is a severe immune-mediated stage of nonalcoholic fatty liver disease that is rapidly becoming the most common etiology requiring liver transplantation (LT), with Hispanics bearing a disproportionate burden. This study aimed to uncover the underlying immune mechanisms of the disparities experienced by Hispanic patients undergoing LT for NASH. Methods. We enrolled 164 LT recipients in our institutional review board-approved study, 33 of whom presented with NASH as the primary etiology of LT (20%), with 16 self-reported as Hispanic (48%). We investigated the histopathology of prereperfusion and postreperfusion biopsies, clinical liver function tests, longitudinal soluble cytokines via 38-plex Luminex, and immune cell phenotypes generated by prereperfusion and postreperfusion blood using 14-color flow cytometry and enzyme-linked immunosorbent assay. Results. Hispanic LT recipients transplanted for NASH were disproportionately female (81%) and disproportionately suffered poor outcomes in the first year posttransplant, including rejection (26%) and death (38%). Clinically, we observed increased pro-inflammatory and apoptotic histopathological features in biopsies, increased AST/international normalized ratio early posttransplantation, and a higher incidence of presensitization to mismatched HLA antigens expressed by the donor allograft. Experimental investigations revealed that blood from female Hispanic NASH patients showed significantly increased levels of leukocyte-attracting chemokines, innate-to-adaptive switching cytokines and growth factors, HMGB1 release, and TLR4/TLR8/TLR9/NOD1 activation, and produced a pro-inflammatory, pro-apoptotic macrophage phenotype with reduced CD14/CD68/CD66a/TIM-3 and increased CD16/CD11b/HLA-DR/CD80. Conclusions. A personalized approach to reducing immunological risk factors is urgently needed for this endotype in Hispanics with NASH requiring LT, particularly in females.